Imagine me - Mafi, Tahereh (2020)
The finale to the Shatter Me series. Juliette Ferrars. Ella Sommers. Which is the truth and which is the lie? Now that Ella knows who Juliette is and what she was created for, things have only become more complicated. As she struggles to understand the past that haunts her and looks to a future more uncertain than ever, the lines between right and wrong -- between Ella and Juliette -- blur. And with old enemies looming, her destiny may not be her own to control. The day of reckoning for the Reestablishment is coming. But she may not get to choose what side she fights on.
Jcat
mod
Keywords: Ferrars, Juliette -- (Fictitious character) -- Fiction; Ability -- Fiction; Soldiers -- Fiction; Dictatorship -- Fiction; Government, Resistance to -- Fiction; Young adult fiction